Revoicing Reflections - Ward Pycock (Networks: An Online Journal for Teacher Research, 2000)
Serendipitously, I stumbled onto revoicing in an article written by O'Connor and Michaels (1996). I often use a speech sequence called the initiate-respond-evaluate (IRE) pattern without being aware of doing it. Many teachers will recognize it -- you pose a question, nominate a student to respond and when they give you the answer you say "What an excellent answer." I've come to realize, through reflection, the restrictions of this speech sequence. In spite of the fact I might even have had a hot topic in class enthusiastically generated by students, I knew that classroom discourse failed to flourish at times. I saw potential in this talking technique called revoicing that might lead the class along the trail of meaningful and thoughtful discussion. It offered a possible alternative to the IRE pattern in classroom discourse.